Analisis Kesalahan Berbahasa Indonesia Tataran Fonologi Pemelajar BIPA di Alekawa Kota Makassar - Mirnawati, Mirnawati; Usman, Usman; Baharman, Baharman (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to describe and analyze the form of Indonesian language errors and their causative factors at the phonological level carried out by BIPA learners in Alekawa, Makassar City. The research data was in the form of oral speech of BIPA learners which contained phonological errors. Data collection was carried out through documentation, observation, and interview techniques. Data is analyzed by the stages of data reduction, data presentation, and conclusion drawn. The results showed significant phonological errors, with the dominant forms of errors including: 1) phoneme changes, such as /a/ to /e/ (e.g.